Turn-taking in the Classroom Session in the Movie Freedom Writers by Richard La Gravanese (2007) - Wahyu Aji Pradana; Malikatul Laila (Universitas Cokroaminoto Palopo, 2020)
Speaker (S) and next speaker or hearer (H) requires a turn-taking process in order to obtain the desired information. This study aims (1) to determine the rules of turn-taking used by S and H in Classroom sessions in the film